MENGELOLA KONFLIK KEPENTINGAN DALAM PROSES PEMBUATAN KEPUTUSAN & FORMULASI KEBIJAKAN DALAM RELOKASI PASAR NGASEM YOGYAKARTA - , ARIEFATOR SUDARNA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The effort from Government of Yogyakarta to organize the city was done in various ways, one of the regulations in public policy is to make relocating program. The Government of Yogyakarta has an understanding with the way they relocating a public area into the new face of Yogyakarta and to make it more presentable and comfortable. The effort is to relocating the Ngasem Market into some place in Yogyakarta called Dongkelan, this is the way from The Government to make Yogyakarta more modernize. In relocation of Ngasem Market there are many actors that involved, like the Government of Yogyakarta, Yogyakarta Palace, the trader in Ngasem Market, the valet services, and many communities from Dongkelan